Locust alert in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
Following the threat of a massive locust infestation in the Western Sahel, FAO director Edouard Saouma launched an international appeal to set in motion an anti-locust campaign for which the estimated cost would be U.S. $ 4 million. This campaign,...